Development of live attenuated Enterovirus 71 vaccine strains that confer protection against lethal challenge in mice - Yee, Isabel Pin Tsin *; Tan, Soon Hao; Ong, Kien Chai; Tan, Kuan Onn *; Wong, Kum Thong; Sharifah Syed Hassan,; Poh, Chit Laa * (Nature Research, 2019)
Besides causing mild hand, foot and mouth infections, Enterovirus A71 (EV-A71) is associated with neurological complications and fatality. With concerns about rising EV-A71 virulence, there is an urgency for more efective vaccines. The live attenuated vaccine (LAV) is a more valuable vaccine as it can elicit both humoral and cellular immune responses. A miRNA-based vaccine strain (pIY) carrying let-7a and miR-124a target genes in the EV-A71 genome which has a partial deletion in the 5′NTR (∆11bp) and G64R mutation (3Dp°l ) was designed. The viral RNA copy number and viral titers of the pIY strain were signifcantly lower in SHSY-5Y cells that expressed both let-7a and miR-124a. Inhibition of the cognate miRNAs expressed in RD and SHSY-5Y cells demonstrated de-repression of viral mRNA translation. A previously constructed multiply mutated strain, MMS and the pIY vaccine strain were assessed in their ability to protect 4-week old mice from hind limb paralysis. The MMS showed higher amounts of IFN-γ ex vivo than the pIY vaccine strain. There was absence of EV-A71 antigen in the skeletal muscles and spinal cord micrographs of mice vaccinated with the MMS and pIY strains. The MMS and pIY strains are promising LAV candidates developed against severe EV-A71 infections.